Criminal recidivism and psychosocial adversity in offense-related subtypes of sexually abusive adolescents. Issue 2 (4th May 2021) - Barra, Steffen; Mokros, Andreas; Landolt, Markus A.; Bessler, Cornelia; Aebi, Marcel
ABSTRACT: Criminal behaviours vary significantly among juveniles who have sexually offended (JSOs). Offense-related subtypes may differ in criminal persistence and inform clinical practice. In the present study, Latent Class Analysis empirically derived four distinct JSO subtypes based on 10 offense/victim characteristics in a comprehensive sample of 670 JSOs ( M age = 14.49, SD age = 1.94): a severe peer/adult-offender subtype (22.4%), a child-offender subtype (30.1%), a touch-offender subtype (27.9%), and a verbal/online-offender subtype (19.6%). Cox regressions indicated that JSOs of the severe peer/adult-offender subtype were at increased risk of sexual and nonsexual criminal recidivism. JSOs of the severe peer/adult-offender subtype as well as the child victim subtype appeared highly burdened with behaviour/social problems and psychosocial adversity/adverse childhood experiences. Our findings show that the variety of offense characteristics, predispositions, and recidivism risks characterising JSOs deserve precise consideration to allow the implementation of effective, individually tailored treatment approaches aimed at reducing future crime.